Sentinel node biopsy after primary chemotherapy in cT2 N0/1 breast cancer patients: Long-term results of a retrospective study. Issue 11 (November 2017) - Martelli, G.; Miceli, R.; Folli, S.; Guzzetti, E.; Chifu, C.; Maugeri, I.; Ferranti, C.; Bianchi, G.; Capri, G.; Carcangiu, M.L.; Paolini, B.; Agresti, R.; et al.
Abstract: Background: It is controversial whether sentinel node biopsy (SNB) is adequate in breast cancer patients who become cN0 after primary chemotherapy. To address this we retrospectively compared outcomes in T2 cases given primary chemotherapy, comparing those given axillary dissection (AD) with those given SNB but no AD if sentinel nodes were clinically negative post-chemotherapy. Methods: We examined overall survival (OS), disease-free survival (DFS), and axillary failure in 317 consecutive cT2 cN0/1 patients given primary chemotherapy followed by quadrantectomy/mastectomy, between January 2002 and December 2007. The approach to the axilla changed over time allowing division into three groups: 101 (31.9%) given upfront AD; 139 (43.8%) given SNB + AD; and 77 (24.3%) given SNB only because the SNs were negative. Results: After median follow-ups of 92 (AD), 99 (SNB + AD) and 72 months (SNB-only), OS (p = 0.131) and DFS (p = 0.087) did not differ between the 3 groups, or between SNB-only and the ypN1 and ypN0 subgroups of SNB + AD, or between the cN0 and cN1 subgroups (before chemotherapy) of the SNB-only group. No SNB-only patient had axillary failure. OS (p = 0.004) and DFS (p = 0.002) were better in patients with complete response than those with partial response or stable/progressive disease. Conclusions: SNB is adequate in T2 patients who are cN0 after primary chemotherapy, irrespective of axillary status before. Better outcomes after complete pathological remission confirm the prognostic importance of response to primary chemotherapy, and suggest that all T2 patients should receive primary chemotherapy.